2001
DOI: 10.21273/horttech.11.2.279
|View full text |Cite
|
Sign up to set email alerts
|

Culture and Use of Black Locust

Abstract: Robinia L. (locust) species are among the most widely planted tree species in the world because they are ornamentally attractive, drought tolerant, fast growing, fix nitrogen, have very hard durable wood, and are adaptable to many sites and climates. Recent taxonomic analysis indicates there are four species, black locust (R. pseudoacacia L.); bristly locust (R. hispida L.); clammy locust (R. viscosa Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 22 publications
0
44
0
1
Order By: Relevance
“…It contributes high levels of nitrogen to the soil through the rhizobium in its roots (DeGomez and Wagner 2001). Tetraploid black locust can be produced by artificial chromosome doubling of diploid black locust.…”
Section: Introductionmentioning
confidence: 99%
“…It contributes high levels of nitrogen to the soil through the rhizobium in its roots (DeGomez and Wagner 2001). Tetraploid black locust can be produced by artificial chromosome doubling of diploid black locust.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that black locust was introduced to Europe in 1600, from where it was brought to China in 1889 (Institute of Forestry Study of Shandong, 1982). Now, black locust is naturalized throughout much of the world's temperate zones owing to its strong adaptability to many abiotic stresses, and its ability to improve and stabilize soils (Keresztesi, 1993;Degomez and Wagner, 2001;Holle et al, 2006). As an economically valuable tree species, black locust is often used for surface mining, timber production, and for livestock browsers (Horton and Christensen, 1981;McCray et al, 1992;Ayers et al, 1996;Burner et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as its connected subterranean root distribution helps to reduce soil erosion and provide nitrogen, black locust has become one of the most ecologically important plant species to reclaim devastated lands and promote soil stabilization (Boring and Swank, 1984a, b;Bożena et al, 2009). The economic and ecological value of this tree enhances the planting of black locust throughout of the world (Woo et al, 1997;Cho, 1999;Degomez and Wagner, 2001;Rédei, 2002;Rédei et al, 2002;Zerbe et al, 2004;Kim and Lee, 2005;Burner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is ornamentally attractive, drought-tolerant, fast growing and adaptable to different sites and climates (DeGomez and Wagner, 2001). The species is widely planted in the United States, Europe and Asia for erosion control, land reclamation of drastically disturbed sites, as windbreaks, for nursery crops, amelioration of sites, honey production and ornamental use (Huntley, 2010).…”
Section: Introductionmentioning
confidence: 99%